Development of a colloidal gold immunochromatographic assay utilizing dual-antibody sandwich method for detecting Orientia tsutsugamushi - Lu, Qingyu; Yu, Shiyin; Wang, Sibo; Cao, Min; Li, Liuxin; Xin, Miao; Tan, Weilong; Qi, Yong; Lu, Yichen; Xiong, Xiaohui (Frontiers in Microbiology, 2025)
A colloidal gold immunochromatographic assay (ICA) based on a dual-antibody sandwich method was developed for the rapid and convenient detection of Orientia tsutsugamushi (O. tsutsugamushi) antigens in the early stages of infection. Monoclonal antibodies designed as 5B3 targeting the conserved region of 56 kDa outer membrane protein in various strains of O. tsutsugamushi were generated through cell fusion and screening techniques and combined with previously prepared polyclonal antibodies as detection antibodies to establish the ICA. Colloidal gold and polyclonal antibody-colloidal gold complexes were synthesized under optimized conditions. The nitrocellulose membrane was treated with 5B3 monoclonal antibody and goat anti-mouse antibody as the test and control lines, respectively. The ICA demonstrated robust sensitivity, with a minimum detection limit of 70.5 ng for the 56 kDa recombinant of the Gilliam strain. Furthermore, a detection limit of 1 × 106 copies/μL DNA of O. tsutsugamushi was determined for both PT and SJ infected cell strains by constructing a relationship between cell number and copy number of the pathogen using a quantitative PCR-based standard curve. The assay also exhibited exceptional specificity, with no false positives observed against other bacterial species, including Escherichia coli, Salmonella, Staphylococcus aureus, and Listeria monocytogenes. In summary, an ICA which is sensitive, specific, and easy to operate was successfully established for the detection of O. tsutsugamushi in scrub typhus, potentially enabling early rapid point-of-care diagnosis of scrub typhus.